"Teaching receptive skills - Teaching in Challenging Circumstances" - Umida Abdushukurova (Zien Journals, 2024)
Teaching receptive skills, including reading and listening, poses unique challenges in environments marked by limited resources, socio-economic disparities, and diverse student needs. This abstract explores effective strategies for educators facing such circumstances. It delves into the adaptation of content, the creation of interactive learning activities, and the cultivation of supportive environments to foster student engagement and comprehension. Additionally, it examines the integration of technology, the importance of differentiation and cultural sensitivity, and the benefits of collaboration with communities. Through these strategies, teachers can navigate challenging circumstances with resilience, ensuring that all students have the opportunity to develop their receptive skills and succeed academically.
Keywords: receptive skills; critical thinking; spontaneity; project-based learning